1997
DOI: 10.1291/hypres.20.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin AT1 Receptor Antagonist on Volume Overload-Induced Cardiac Gene Expression in Rats.

Abstract: The present study was undertaken to examine the effects of volume overload on cardiac gene expression and the possible role of angiotensin ATl receptor in such expression. Cardiac volume overload was prepared by abdominal aortocaval shunt in rats. Rats with aortocaval shunt were treated with 1) vehicle, 2) an angiotensin ATi receptor antagonist, CS-866 (10 mg/kg/d), or 3) an angiotensin-converting enzyme inhibitor, temocapril (10 mg/kg/d), for 7 days. Cardiac tissue mRNA was measured by Northern blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…6,18,19 By contrast, decreased synthesis or expression of ␣-cardiac MHC can result from either volume or pressure loading, where the renin-angiotensin II system mediates hemodynamic loading and compensatory hypertrophy. 25,40,50,56 Current data and other reports therefore support the idea that deflazacort-induced hypertrophy and increased ␣-cardiac MHC occurred largely independent of the renin-angiotensin system. 21,27,35,57 Protection from contraction-induced damage may derive from combined increases in laminin, tau- rine, and bFGF that could stabilize membranes, mediate calcium homeostasis, and protect against peroxidation injury, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…6,18,19 By contrast, decreased synthesis or expression of ␣-cardiac MHC can result from either volume or pressure loading, where the renin-angiotensin II system mediates hemodynamic loading and compensatory hypertrophy. 25,40,50,56 Current data and other reports therefore support the idea that deflazacort-induced hypertrophy and increased ␣-cardiac MHC occurred largely independent of the renin-angiotensin system. 21,27,35,57 Protection from contraction-induced damage may derive from combined increases in laminin, tau- rine, and bFGF that could stabilize membranes, mediate calcium homeostasis, and protect against peroxidation injury, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…The ratio of ␣-to ␤-cardiac myosin isoforms can provide an index of oxidative and glycolytic capacity, respectively. 18,19,25,50,57 The ␣-cardiac myosin heavy chain (MHC) distribution and concentration may also change during disease and treatment with glucocorticoids. 12 Proton magnetic resonance spectroscopy (H-NMRS) can detect metabolic changes of disease and treatment.…”
mentioning
confidence: 99%
“…In this study, treatment of animals with losartan was found to partially prevent cardiac hypertrophy, which is in agreement with other investigators as well as with other AT 1 receptor antagonists [27][28][29][30][31][32] using this model. While some of these investigators [27,28] also reported attenuation of the increased expression of a number of cardiac genes including atrial natriuretic peptide and collagen types I and III in volume overloaded hearts, the attenuation of cardiac hypertrophy may be related to partial attenuation of some of the PLC isozyme gene expression by the action of losartan.…”
Section: Discussionsupporting
confidence: 93%
“…While some of these investigators [27,28] also reported attenuation of the increased expression of a number of cardiac genes including atrial natriuretic peptide and collagen types I and III in volume overloaded hearts, the attenuation of cardiac hypertrophy may be related to partial attenuation of some of the PLC isozyme gene expression by the action of losartan. This indicates that RAS is partially involved in inducing cardiac hypertrophy and increases in specific PLC isozyme gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…CS-866, [17][18][19] a selective nonpeptide AT 1 receptor antagonist, and temocapril hydrochloride, 20 an ACE inhibitor, were provided by Sankyo Co, Ltd. FR172357, 21,22 a nonpeptide bradykinin B 2 receptor antagonist, was provided as a gift by Fujisawa Pharmaceutical Co, Ltd. These drugs were suspended with 0.5% carboxymethylcellulose.…”
Section: Drugsmentioning
confidence: 99%